Learning the single-dominant modal system on resonant sloshing in a rectangular tank - Milyaev, A.O.; Timokha, A.N. (Reports of the National Academy of Sciences of Ukraine, 2022)
A machine learning technique is proposed to derive the damping rate functions in the co-called single-dominant modal system describing the resonant liquid sloshing in a rectangular tank performing harmonic longitudinal motions. Its implementation is demonstrated for the steady-state (periodic) resonance waves when the modal system admits an analytical asymptotic solution depending on the introduced damping rate functions. Recent experiments by Bäuerlein & Avila (2021) are employed to show that the viscous damping of the higher natural sloshing modes matters, and the damping functions depend on the wave amplitude.